Magnetic diffusion and interaction effects on ultrahigh energy cosmic rays: Protons and nuclei - Gonzalez, Juan Manuel (2021)
The flux of ultrahigh energy cosmic rays reaching the Earth is affected by the interactions with the cosmic radiation backgrounds as well as with the magnetic fields that are present along their trajectories. We combine the simprop cosmic ray propagation code with a routine that allows us to account for the average effects of a turbulent magnetic field on the direction of propagation of the particles. We compute in this way the modification of the spectrum which is due to the magnetic horizon effect, both for primary nuclei as well as for the secondary nuclei resulting from the photodisintegration of the primary ones. We also provide analytic parametrizations of the attenuation effects, as a function of the magnetic field parameters and of the density of cosmic ray sources, which make it possible to obtain the expected spectra in the presence of the magnetic fields from the spectra that would be obtained in the absence of magnetic fields. The discrete nature of the distribution of sources with finite density also affects the spectrum of cosmic rays at the highest energies where the flux is suppressed due to the interactions with the radiation backgrounds, and parametrizations of these effects are obtained.